2021
DOI: 10.1007/s11481-021-10022-7
|View full text |Cite
|
Sign up to set email alerts
|

Drugs and Bugs: The Gut-Brain Axis and Substance Use Disorders

Abstract: Substance use disorders (SUDs) represent a significant public health crisis. Worldwide, 5.4% of the global disease burden is attributed to SUDs and alcohol use, and many more use psychoactive substances recreationally. Often associated with comorbidities, SUDs result in changes to both brain function and physiological responses. Mounting evidence calls for a precision approach for the treatment and diagnosis of SUDs, and the gut microbiome is emerging as a contributor to such disorders. Over the last few centu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 324 publications
(394 reference statements)
1
22
0
Order By: Relevance
“…For example, Shanahan et al found increased relative abundance of Firmcutes and Actinobacteria , with lower levels of Bacteroidetes ( Prevotella ) and Proteobacteria ( Neisseria ) [ 84 ]. Other studies have found an increase in Proteobacteria and Bacteroidetes , as well as Clostridia and Prevotella , in smokers [ 82 ]. The effects of nicotine on the GM may depend on the mode of intake and individual factors such as sex, diet, and genetics [ 82 ].…”
Section: Lifestyle Factors Affecting Gm and Mental Health: Diet Physi...mentioning
confidence: 98%
See 4 more Smart Citations
“…For example, Shanahan et al found increased relative abundance of Firmcutes and Actinobacteria , with lower levels of Bacteroidetes ( Prevotella ) and Proteobacteria ( Neisseria ) [ 84 ]. Other studies have found an increase in Proteobacteria and Bacteroidetes , as well as Clostridia and Prevotella , in smokers [ 82 ]. The effects of nicotine on the GM may depend on the mode of intake and individual factors such as sex, diet, and genetics [ 82 ].…”
Section: Lifestyle Factors Affecting Gm and Mental Health: Diet Physi...mentioning
confidence: 98%
“…Other studies have found an increase in Proteobacteria and Bacteroidetes , as well as Clostridia and Prevotella , in smokers [ 82 ]. The effects of nicotine on the GM may depend on the mode of intake and individual factors such as sex, diet, and genetics [ 82 ].…”
Section: Lifestyle Factors Affecting Gm and Mental Health: Diet Physi...mentioning
confidence: 98%
See 3 more Smart Citations